Multislice-CT of the Abdomen - Zech, Christoph Johannes; Bartolozzi, Carlo; Baron, Richard; Reiser, Maximilian F. (Springer Berlin Heidelberg, 2012)
This book provides a lucid summary of modern multislice CT imaging of the abdomen, with a focus on the essential imaging findings. After a concise technical introduction, the most important abdominal diseases are described and illustrated with high-quality images. Sections are devoted to the liver and biliary system, the pancreas and spleen, the kidneys and urogenital system, and the bowel and peritoneal cavity. Throughout, key differential diagnostic features are highlighted. The editorial team is composed of internationally renowned radiologists from Europe and the United States, and all chapters have been written by recognized experts in the topic under consideration. Multislice CT of the Abdomen will serve as an excellent reference for radiologists participating in further professional training and will prove an ideal source of information for all who wish to deepen their personal knowledge of the subject
Keywords: Imaging / Radiology; Diagnostic Radiology; Radiology; Bauchkrankheit; Spiral-CT; Aufsatzsammlung